2017
DOI: 10.1177/1045389x17711790
|View full text |Cite
|
Sign up to set email alerts
|

Selective damage sensing in multiscale hierarchical composites by tailoring the location of carbon nanotubes

Abstract: The selectivity in composite damage sensing using the electrical resistance approach is investigated by deliberately placing multiwall carbon nanotubes (MWCNTs) dispersed within the matrix or deposited onto the fiber surface. To this aim, unidirectional glass fiber/carbon nanotube/vinyl ester specimens with fibers oriented along (0°) and transverse (90°) to the loading direction are subjected to quasi-static tension up to failure. The electrical resistance changes in the composite are correlated to the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Due their outstanding physical properties, carbon nanotubes (CNTs) have been of great interest for the scientific and industrial communities, resulting in an increased interest for their application in smart materials with sensing and/or actuating capabilities. [ 1 ] For their use as sensors or actuators in smart materials, CNTs have been used in the form of films or arrays, [ 2,3 ] deposited or grown on substrates, [ 4,5 ] as well drawn, twisted, and used in the form of continuous fibers or yarns (carbon nanotube yarns [CNTYs]). [ 6,7 ] A CNTY is a micron‐size diameter continuous fiber comprising thousands of CNTs in its cross‐section.…”
Section: Introductionmentioning
confidence: 99%
“…Due their outstanding physical properties, carbon nanotubes (CNTs) have been of great interest for the scientific and industrial communities, resulting in an increased interest for their application in smart materials with sensing and/or actuating capabilities. [ 1 ] For their use as sensors or actuators in smart materials, CNTs have been used in the form of films or arrays, [ 2,3 ] deposited or grown on substrates, [ 4,5 ] as well drawn, twisted, and used in the form of continuous fibers or yarns (carbon nanotube yarns [CNTYs]). [ 6,7 ] A CNTY is a micron‐size diameter continuous fiber comprising thousands of CNTs in its cross‐section.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Due et al 17 incorporated graphene/epoxy interleaves within carbon fiber laminated composites for delamination toughening and monitoring of crack damage under quasi-static fracture loading. Ku-Herrera et al 18 deposited CNTs selectively in unidirectional glass fiber/vinyl ester composites and investigated damage sensing using electrical resistance measurements. They later compared the electrical response to that of acoustic emission events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for hierarchical multiscale composites comprising continuous structural fibers, a polymer matrix, and electroconductive nanostructures such as CNTs, the CNT conductive network can be formed on both the fiber and/or within the polymer matrix. For thermosetting matrices, Ku-Herrera et al (2018) have shown that the preferential location of CNTs within the hierarchical composite plays a key role on its piezoresistive response. However, this piezoresistive response has not been explored for a material system comprising PP and aramid fibers.…”
Section: Introductionmentioning
confidence: 99%